Caribbean Slab Segmentation Beneath Northwest South America Revealed by 3‐D Finite Frequency Teleseismic P‐Wave Tomography. (6th April 2021) - Cornthwaite, John; Bezada, Maximiliano J.; Miao, Wenpei; Schmitz, Michael; Prieto, Germán A.; Dionicio, Viviana; Niu, Fenglin; Levander, Alan
Abstract: The Caribbean plate subducts beneath northwest South America at a shallow angle due to a large igneous province that added up to 12 km of buoyant crust. The overriding plate lacks volcanism and exhibits Laramide‐style uplifts over 500 km from the trench. Here, we illuminate the subduction structures through finite frequency teleseismic P‐wave tomography and connect those structures to the Laramide‐style deformation on the overriding plate. We use a new data set collected from the Caribbean‐Mérida Andes seismic experiment comprised of 65 temporary broadband stations integrated with permanent stations from the Colombian and Venezuelan national networks. We identify three segments of subducting Caribbean plate with one segment completely detached from the surface. The timing of the detachment aligns with other regional events, including the uplift of the Mérida Andes, about 10 Ma. Slab buoyancy post‐detachment likely resulted in recoupling with the overriding plate, reactivation of Jurassic‐aged rift structures and subsequent uplift of the Mérida Andes. Mantle counterflow over the broken segment induced by rollback of the attached slab likely contributed to the uplift of the Mérida Andes. We conclude that the northern limit of subduction lies south of the Oca‐Ancón fault, though the fault itself may be the surface expression of the boundary. The southern limit of subduction lies south of our study area. Plain Language Summary: At the convergent boundary between the southern Caribbean and northwest South America the Caribbean plate dips, or subducts, beneath South America at angles less than 30° for up to ∼300 km inland before steepening. Such low‐angle subduction systems are unique because they produce mountains hundreds of kilometers inland. Using new data collected by the Caribbean‐Mérida Andes seismic array, which continuously recorded earthquakes for two years, we imaged the Caribbean plate to depths of 660 km and identified at least three segments, including a segment detached from the surface. The timing of the detachment ∼5–15 million years ago aligns with the uplift of the Mérida Andes of Venezuela ∼500 km inland. Both the attached and detached segments interacted with the underside of South America, compressing parts of it, and causing uplift of the Mérida Andes. The northern limit of subduction lies south of the Oca‐Ancón fault of northern Colombia and Venezuela. The southern expanse of subduction includes the Bucaramanga earthquake cluster, but the boundary lies south of our study area. By understanding how the actively subducting plate, the Caribbean, deforms the upper plate, South America, we can better assess seismic risk and understand similar systems that are no longer active. Key Points: At least three Caribbean segments subduct under South America, one detached under the Merida Andes. Detachment due to lithospheric weakness Post‐break recoupling and rollback of slab contribute to uplift of Mérida Andes Northern subduction boundary identified